2018
DOI: 10.1021/acs.molpharmaceut.8b00541
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Artefenomel (OZ439) with Milk during Digestion: Insights into Digestion-Driven Solubilization and Polymorphic Transformations

Abstract: Milk has been used as a vehicle for the delivery of antimalarial drugs during clinical trials to test for a food effect and artefenomel (OZ439) showed enhanced oral bioavailability with milk. However, the nature of the interaction between milk and OZ439 in the gastrointestinal tract remains poorly understood. To understand the role of milk digestion on the solubilization of OZ439 and polymorphism, we conducted real-time monitoring of crystalline drug in suspension during in vitro intestinal lipolysis of milk c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(73 citation statements)
references
References 46 publications
2
70
1
Order By: Relevance
“…The SAXS pattern for the digestion of OZ439 only (no FQ) in milk is also included in panel b for comparison. 6 As was expected from the behavior of the individual drugs, disappearance of the characteristic FQ peak and polymorphic transformation of OZ439-FB from form 1 to form 2 occurred concurrently. However, it was evident that the kinetics of formation of OZ439-FB form 2 were different than in the case of OZ439 alone, where addition of FQ induced an earlier formation of the FB form 2.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…The SAXS pattern for the digestion of OZ439 only (no FQ) in milk is also included in panel b for comparison. 6 As was expected from the behavior of the individual drugs, disappearance of the characteristic FQ peak and polymorphic transformation of OZ439-FB from form 1 to form 2 occurred concurrently. However, it was evident that the kinetics of formation of OZ439-FB form 2 were different than in the case of OZ439 alone, where addition of FQ induced an earlier formation of the FB form 2.…”
Section: Resultsmentioning
confidence: 64%
“…No crystalline OZ439-FB form 2 peak was seen during the dispersion of OZ439 in milk in the absence of FQ. 6…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has previously shown the role of milk digestion on the solubilisation of a drug and its polymorphism (Salim et al, 2018). In this study, we aim to understand the effect of digestion of milk and infant formula lipids on the solubilisation of a drug when presented as a solid dosage form.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of poorly soluble lipophilic drugs, digestion is a crucial component as the nature of the lipids and their digestion products promotes drug solubilisation and transport to the systemic circulation (Pouton, 2006, Feeney et al, 2016, Kaukonen et al, 2004, Mu et al, 2013). It has been recently shown that the digestion of milk can be a particularly effective way to drive solubilisation of co-administered drug (Salim et al, 2018).…”
Section: Introductionmentioning
confidence: 99%